The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.04.02.022525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved and Divergent Modulation of Calcification in Atherosclerosis and Aortic Valve Disease by Tissue Extracellular Vesicles

Abstract: 53 54 Background: Fewer than 50% of patients develop calcification of both atherosclerotic plaques 55 and aortic valves, implying differential pathogenesis. While circulating extracellular vesicles 56 (EVs) act as biomarkers of cardiovascular diseases, tissue-entrapped EVs associate with early 57 mineralization, but their contents, function, and contributions to disease remain unknown. 58 59 Results: Global proteomics of human carotid artery endarterectomies and calcified aortic valves 60 from a total of 27 do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Increased levels of MMPs during monocyte/macrophage activation seem to be depended on mitogen activated protein kinases, phosphoinositide-3-kinase and inhibitor of ÎșB kinase-2 ( 51 ). Our research group has shown that inflammation and its downstream events are the key factors in mitral heart valve disease and could serve as targets for regenerative medicine ( 25 , 26 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of MMPs during monocyte/macrophage activation seem to be depended on mitogen activated protein kinases, phosphoinositide-3-kinase and inhibitor of ÎșB kinase-2 ( 51 ). Our research group has shown that inflammation and its downstream events are the key factors in mitral heart valve disease and could serve as targets for regenerative medicine ( 25 , 26 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have also utilized miRNA-mRNA target networks to link AV extracellular vesicle–borne miRNAs quantified by small RNA-seq to their predicted high-confidence gene targets in recipient cells, and integrated vesicular miRNA-seq and proteomics via pathways networks to predict the cumulative impact of extracellular vesicle cargoes and prioritize candidate molecules for drug target validation. 46 Others have employed network analyses to screen for compounds with therapeutic potential: targeted RNA-seq coupled with machine learning tactics has been utilized to map the gene network disrupted in human NOTCH1 -haploinsufficient iPSC-derived endothelial cells and to screen molecules for their network topology-correcting effects. 47 Strikingly, XCT790, an inverse estrogen-related receptor α agonist, showed network-restorative features, sufficient to prevent CAVD initiation and progression in Notch1/mTR G 2 mice.…”
Section: Towards a Holistic Understanding Of Cavd: Systems Biology An...mentioning
confidence: 99%
“…We have recently taken a similar approach to assess the vesiculome of diseased carotid and valvular tissue. 158 We established a method to isolate tissue resident EVs from human surgically resected fibrocalcific cardiovascular tissues. In calcified aortic valves and carotid endarterectomy specimens, tissue entrapped EVs could be isolated using a combination of approaches to overcome the challenges presented by the complex and fibrous nature of the tissue.…”
Section: Utilization Of Multi-omics and Network Medicine To Facilitat...mentioning
confidence: 99%
“…We have recently taken a similar approach to assess the vesiculome of diseased carotid and valvular tissue 158 . We established a method to isolate tissue resident EVs from human surgically resected fibrocalcific cardiovascular tissues.…”
Section: Where We Are Going and What Is Holding The Field Back?mentioning
confidence: 99%